FENOMENA BODY DISSATISFACTION PADA PEREMPUAN ANGGOTA FITNESS CENTRE - Happy Yuanita; Monique Elizabeth Sukamto (Universitas Negeri Surabaya, 2013)
Body dissatisfaction is a negative evaluation of the body that occurs due to the difference between the real body size and shape and the ideal one. Many women are dissatisfied with their body shape, which can be caused by the physical changes in each developmental stages and the prevailing beauty standard. One criteria of a beautiful woman is slim body. Body Mass Index (BMI) is the most common standard to evaluate ones body weight. One effort many women do to achieve the ideal body shape and weight is to exercise in fitness centre. This study was aimed to evaluate the differences in body dissatisfaction among women who were members of fitness centre in terms of the developmental stages and level of obesity. Subjects were 150 women who became a member of fitness centre